Aplicación de dispositivos móviles en la medición de los niveles de radiación ultravioleta y su validación en el distrito de Chulucanas región Piura Perú - Dedios Mimbela, Ninell Janett (Editorial Bonaventuriana, 2018)
App is a software application installed on mobile devices to facilitate achievement of tasks, operations or management to a daily user. This research develops an analysis of the efficiency of mobile applications in the measurement of ultraviolet radiations levels in Chulucanas district, in order to verify the reliability of the data obtained and foster a culture of prevention to sun overexposure in the chulucanense population and prevent UV radiation-related illnesses. The methodology employed considers the information coming from three free download applications mobile previously selected, World UV, Uv-indeks and NoTeQuemes. UV monitoring were carried out in the following three geographic areas, Chulucanas, Chapica Campanas, Papelillo town. The measurement was carried every two hours in total of five times every day starting 8 am ending at 4:00 in a period of a month. The results obtained indicate the hourly and daily influence on the development of the level of ultraviolet radiation. from observed sector, it is determined that the hour of greatest impact occurs at noon solar day, as regards the most suitable type of mobile application UV Indeks is considered to be the one with the best response according to the results obtained in the consulted bibliography.